Social costs of transport in Switzerland. Measuring the impact of transport on the society and quantifying compliance with the polluter pays principle. - Gigon, Christian; Quandt, Alexandra (Trialog Publishers, 2019)
What is the cost of transport in Switzerland? What are the drivers of transport cost and who pays for it? The "Statistics on the costs and funding of transport" compiled by the Swiss Federal Statistical Office answers these questions for the transport modes road, rail, air and inland waterways. The statistics take into account not only financial expenditures but also the intangible costs of transport-related accidents or damages to health and the environment.
Keywords: Verkehr; Verkehrskosten; Externe Kosten; Umweltschaden; Verursacherprinzip; Straßenverkehr; Verkehrsmittel; Verkehrsinfrastruktur; Kostenverteilung; Finanzierung; Statistik